Molecular epidemiology of lung cancer - Christiani, David (Henry Stewart Talks, 2007)
The influence of host factors on individual susceptibility to tobacco smoke, The pleiotropic genes that control activation (Phase I) and detoxification (Phase II) of potential carcinogens, Effects of the metabolism of environmental compounds on the lipophilic properties of a molecule and the introduction of electronegative moieties within the molecule on carcinogenic potential, Other susceptibility factors related to defects in DNA repair, alterations in tumor suppressor genes and alterations in tumor invasiveness factors, Polymorphisms in genes and the association of this with lung cancer development, The role of inherited polymorphisms of genes involved in xenobiotic metabolism, DNA repair and tumor suppression/invasion (alone and in combination) in lung cancer risk, and modification of this risk by environmental factors such as smoking and diet
Archived at 2021/02/25